ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI BAWANG MERAH (Allium cepa L.) DI KECAMATAN MIJEN KABUPATEN DEMAK - Inayah Rahmawati Putri Utami; Sri Wahyuningsih; Shofia Nur Awami; Renan Subantoro (MEDIAGRO, 2021)
Welfare is the final goal of the process of agricultural development in an area. The consumption pattern and the amount of consumption of farmer's household is an indication of the achievement of welfare in a farmer's household. This study aims to determine the consumption patterns of shallots farmers in the Pasir Village, determine the level of energy and protein adequacy of the household of the shallots farmers in the Sand Village and determine the level of food security of the shallots farmers in the Pasir Village (Johnsson and Toole model). Methods of data analysis were carried out using percentages of food expenditure, levels of energy and protein consumption, and cross indicators of food security levels. Sampling was done by purposive sampling method by dividing the two strata, strata I were 71 farmers and strata II were 33 farmers. The results of this study indicate that the percentage of food expenditure (PF) for strata I farmers is higher at 53.53% than strata II farmers at 40.15%. Shallot farmers in Pasir Village have been able to meet the energy and protein needs for household members, but have not yet reached the recommended AKE rate for WNPG XI in 2018 which is 2100 kcal / person / day. The food security status of strata I and II onion farmers in Pasir Village, Mijen District, Demak Regency is classified in the category of food security, namely the proportion of food expenditure ( 80%). Keywords: Consumption Pattern, Shallot, Energy, Protein.